A Systematic Review of Factors Related to Employment Outcomes for Adults with Visual Impairments. (November 2019) - Lund, Emily M.; Cmar, Jennifer L.
Introduction: The purpose of this study was to conduct a systematic review of survey-based research on predictors or correlates of employment outcomes for individuals with visual impairments (i.e., those who are blind or have low vision). Methods: We used a three-pronged systematic search process to identify quantitative, English, peer-reviewed articles published from 1990 to August 2018 that included analyses of factors related to employment in American adults with visual impairments. We coded all included articles for sample parameters, participant characteristics, quality indicators (QIs), and study outcomes. Results: Thirteen articles were included in the review. The majority of studies met few, if any, QIs. Education level, braille reading medium, and attending integrated or public schools were significantly associated with employment outcomes in most analyses in which those variables were included. Other demographic and disability-related variables were generally not associated with employment or yielded inconsistent results across studies. Psychosocial, service, and miscellaneous variables were included less frequently and were generally not associated with employment or yielded mixed results, with a few exceptions. Discussion: Based on our quality indicator ratings, there were consistent methodological weaknesses in this body of literature. Small samples ( N = 200 or fewer) were prevalent across studies, which limits both generalizability and statistical power. Use of nonrepresentative and nonnational samples further limits generalizability of the results, and a lack of longitudinal studies hinders our ability to draw causal inferences. More high-quality employment research is needed, particularly in the areas of braille, transportation self-efficacy, and other psychosocial factors. Implications for practitioners: Despite the methodological issues identified in the included studies, results support findings from other systematic reviews regarding the importance of educational advancement for individuals with visual impairments. Practitioners should encourage individuals with visual impairments who do not have college degrees to explore options for postsecondary education.